Smoke-free in 30 days : the pain-free, permanent way to quit - Seidman, Daniel F. (New York, NY : Simon & Schuster, 2010)
'In a comprehensive, 30-day program, Dr. Seidman explains how to retrain your brain, take advantage of all the tools at your disposal, and end the month smoke-free and feeling stronger than ever!'--from cover.
'A Fireside book.'
Includes bibliographical references (p. [211]-212) and index.
Keywords: Smoking Cessation; Nicotine addiction -- Treatment; Smoking Cessation -- Popular Works